Tindak Tutur Ilokusi Ekspresif dalam Cuitan Akun Twitter - Herra Rodearni; Irwan Siagian (Departement of Mathematics Education, 2023)
This study aims to describe the forms of expressive illocutionary speech acts found in tweets from Twitter accounts. This study contains expressive illocutionary utterances which are analyzed by researchers based on the data that has been collected. The data is sourced from a Twitter account which is seen based on the tweets of Twitter users. The method in this study is a qualitative descriptive research in the form of written sentences. Data collection techniques in this study used observing, recording, and documentation. Listening and note-taking techniques are carried out by researchers by sorting and selecting data to be analyzed. While documentation was included by the researchers in the form of screenshots of tweets from Twitter account users. Data analysis techniques are performed by reducing data, presenting data, interpreting data, and drawing conclusions. The analysis that is carried out always involves a literature study process in order to strengthen evidence related to data that has been collected theoretically, so as to produce valid and reliable conclusions. In the results of this study, 24 data were found which were classified into expressive illocutionary speech acts. The 24 data describe the expression of the speaker's psychological attitude towards the situation implied in the illocutionary which consists of; 1) say thank you; 2) congratulate; 3) forgive; 4) censure; 5) praise; and 6) express condolences. This research can be useful in the learning process by adding insight and knowledge for educators and students regarding the study of pragmatics in speech acts and the relationship between speakers and interlocutors in expressive illocutionary speech.